Regime switches in the risk-return trade-off - Eric Ghysels; Pierre Guérin; Massimiliano Marcellino (Bank of Canada, 2013)
This paper deals with the estimation of the risk-return trade-off. We use a MIDAS model for the conditional variance and allow for possible switches in the risk-return relation through a Markov-switching specification. We find strong evidence for regime changes in the risk-return relation. This finding is robust to a large range of specifications. In the first regime characterized by low ex-post returns and high volatility, the risk-return relation is reversed, whereas the intuitive positive risk-return trade-off holds in the second regime. The first regime is interpreted as a flight-to-quality regime.
Keywords: G10; G12; 330; Economic and statistical models; Financial markets